Compatibility of Data Transfer between CAD Applications - Kuchynkova, Hana (Radioengineering Society, 2003)
Compatibility of data transfers between individual CAD programs is topical when in another program we need to use a drawing or a 3D model created in a program that uses a different modeling kernel. The paper characterizes features and structures of existing CAD formats, problems in their transfer, it notes the export/import conversion through the IGES, SAT, STEP and STL formats. It takes a closer look at using the STL format for visualization and animation.
Keywords: Data transfer; compatibility; data format; Boolean functions; optimization; faces; objects; animation